The Development of Plantapicard Education Game Learning Media for Tenth Grade Students of Senior High School - Mahfiroh, Miskiyati Saroya; Purwantoyo, Eling; Rudyatmi, Ely (FMIPA UNNES, 2020)
This research was conducted in SMA Negeri 1 Randudongkal. This research uses research and development design (R& D). The product trial was conducted in class X MIPA 2 and X MIPA 3 by Sampling Purposive method and experimental design, Nonequivalent Control Group Design. The results of the assessment of educational plantapicard game expert obtained very valid with the value 92.5% for material and 95% for media. According to experts, learning media developed plantapicard education game has the advantage i.e. the size of a small book so practical use when learning, interesting book, creative design, and language that is easy and communicative so as to create student interest in understanding learning. From the results of the teacher and student’s responses questionnaires to the product, the test gets positive feedback with very good criteria. Mastery learning is obtained from the analysis with value of 86.11% for X MIPA 2 and 50% for X MIPA 3. Students activity in the learning process using Plantapicard Education Game increases at each meeting. Most students meet the active and highly active criteria. This study shows that Plantapicard Education Game in Plantae is valid, practical and effective use as a learning medium.